Optimal imaging windows of indocyanine green‐assisted near‐infrared dental imaging with rat model and its comparison to X‐ray imaging. Issue 6 (9th March 2020) - Li, Zhongqiang; Hartzler, Thomas; Ramos, Alexandra; Osborn, Michelle L.; Li, Yanping; Yao, Shaomian; Xu, Jian
Abstract: In this study, we used rat animal model to compare the efficiency of indocyanine green (ICG)‐assisted dental near‐infrared fluorescence imaging with X‐ray imaging, and we optimized the imaging window for both unerupted and erupted molars. The results show that the morphology of the dental structures was observed clearly from ICG‐assisted dental images (especially through the endoscope). A better image contrast was easily acquired at the short imaging windows (<10 minutes) for unerupted and erupted molars. For unerupted molars, there is another optimized imaging window (48‐96 hours) with a prominent glow‐in‐the‐dark effect: only the molars remain bright. This study also revealed that the laser ablation of dental follicles can disrupt the molar development, and our method is able to efficiently detect laser‐treated molars and acquire the precise morphology. Thus, ICG‐assisted dental imaging has the potential to be a safer and more efficient imaging modality for the real‐time diagnosis of dental diseases. Abstract : In this study, we used rat animal model to compare the efficiency of indocyanine green (ICG)‐assisted dental near‐infrared fluorescence imaging with X‐ray imaging and we optimized the imaging window for both unerupted and erupted molars. The results show that the morphology of the dental structures was observed clearly from ICG‐assisted dental images. This study also revealed that the laser ablation of dental follicles can disrupt the molar development, and our method is able to efficiently detect laser‐treated molars and acquire the precise morphology.